EFFECT OF FUNGICIDES ON PROLINE CONTENT OF NOSTOC SP - G. V. N. S. DEVIRAM; R. GYANA PRASUNA (International Journal of Pharma and Bio Sciences, 2012)
This study describes the toxic effects and most widely used fungicides on the intracellular proline content of cyanobacterium Nostoc sp. In spite of chlorophyll reduction the intracellular proline content increased in the presence of plant protecting chemicals. The intracellular proline content accumulation was more in the presence of salt stress (300mM) and slightly less with fungicides. Mancozeb at 3.0µg/ml other fungicides also increased the proline content but with gradual increase in fungicide (3.5 - 5.0 µg/ml) concentration led to a significant change, maximum yellowing was observed resulting in proline content degradation. The order of toxicity was Mancozeb> Difeconazole> Ediphenphos> Hexaconazole.